Class in Australian higher education: The university as a site of social reproduction. (September 2020) - Bunn, Matthew; Threadgold, Steven; Burke, Penny Jane
Explanations of inequality in higher education primarily use the dominant language of institutional equity discourses, such as low socio-economic status (LSES), 'under-represented' or 'non-traditional' backgrounds. We argue that analysis that relies on a static series of objective categories regularly fails to account for the symbolic-historical conditions that have produced class boundaries. In acknowledging this, one of the challenges in higher education research is to illuminate how working-class understanding of education systems is brought into universities, and how it relates to, and is contested by, the dominant middle-class culture of the university. We propose a Bourdieusian-inspired class analysis be adopted for Australian higher education that focuses more closely on the way in which symbolic power is distributed through the misrecognition of species of capital as symbolic capital. Using this approach we argue that universities, rather than ameliorating class difference, are a poorly understood site of its generation.